Correction of rat acute cholangitis using water-soluble C60 fullerene nanoparticles - Kuznietsova, H.M.; Dziubenko, N.V.; Rybalchenko, T.V.; Ogloblya, O.V.; Rybalchenko, V.K. (Reports of the National Academy of Sciences of Ukraine, 2018)
The effects of water-soluble biocompatible C60 fullerenes (C60FAS) when applied intraperitoneally or per os on the liver function under rat α-naphthyl-isothiocyanate-induced cholangitis model are investigated. C60FAS when administered per os normalizes the direct bilirubin and ALT. Additionally, total bilirubin and ALP are normalized under C60FAS intraperitoneal injection, by indicating the attenuation of disease symptoms severity. Thus, the partial correction of cholangitis-induced liver failure caused by C60FAS is demonstrated, and the higher efficacy of C60FAS intraperitoneal injection is concluded.